2018
DOI: 10.1002/rmv.2021
|View full text |Cite
|
Sign up to set email alerts
|

Research advancements in the neurological presentation of flaviviruses

Abstract: Summary Owing to the large‐scale epidemic of Zika virus disease and its association with microcephaly, properties that allow flaviviruses to cause nervous system diseases are an important area of investigation. At present, although potential pathogenic mechanisms of flaviviruses in the nervous system have been examined, they have not been completely elucidated. In this paper, we review the possible mechanisms of blood‐brain barrier penetration, the pathological effects on neurons, and the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…Looking more closer to the single substitutions, one amino acid exchange (R346A) may have relevance to the binding affinity to the host receptor (heparan sulphate, HS) since the exchange lies on domain III as binding domain and implies strong changes in van-der-Waals radius as well as in hydrophobicity, polarity and acid dissociation constant of residue (Additional file 5: Table S2). However, more distant amino acid residues 308 and 311 on the upper lateral surface of domain III of TBE complex viruses have been identified as determinants of neurovirulence and neuro-invasiveness [29,41,60]. In addition, the R346A substitution was detected in all seven OWH isolates, so that the functional meaning remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Looking more closer to the single substitutions, one amino acid exchange (R346A) may have relevance to the binding affinity to the host receptor (heparan sulphate, HS) since the exchange lies on domain III as binding domain and implies strong changes in van-der-Waals radius as well as in hydrophobicity, polarity and acid dissociation constant of residue (Additional file 5: Table S2). However, more distant amino acid residues 308 and 311 on the upper lateral surface of domain III of TBE complex viruses have been identified as determinants of neurovirulence and neuro-invasiveness [29,41,60]. In addition, the R346A substitution was detected in all seven OWH isolates, so that the functional meaning remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Three out of six of our identified amino acid exchanges occurred within a fragment reaching from position 305 to 346. In this part of domain III, mutations have been reported that affect neuro-invasiveness of Japanese encephalitis virus and yellow fever virus [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a human fetal‐like forebrain organoid model, treatment with 25 µM of HH for 3 days was effective in reducing the percentage of cells infected with ZIKV. This is especially important as ZIKV infection is often associated with neurological disorders 18 . This finding was further shown in severe combined immunodeficiency beige (SCID‐beige) mice, where immunohistochemical analysis revealed that HH was able to reduce infection in various regions of the brain.…”
Section: Inhibitors With Unknown Targetsmentioning
confidence: 89%
“…ZIKV patients who are pregnant also are at increased risk of giving birth to children with congenital Zika syndrome, a group of birth defects, including fetal microcephaly brain calcification, and abnormal brain development 16,17 . These complications are not observed in other flaviviral infections, which makes early diagnosis and treatment of ZIKV infections of paramount importance 18 …”
Section: Introductionmentioning
confidence: 99%